Nós também fazemos parte desta história": memória de mulheres negras em Brasília - Cardoso, Elna Dias (2018)
This work aims to analyze the narratives of black women about the process of construction and consolidation of Brasília, presenting empirical data for a sociological analysis of memory and its intersections between gender and race / color through documentary analysis and ten Life stories. The problematizing questions of the research were: How are black women presented in the symbolic and cultural repertoire about the construction and consolidation of Brasília (1956-1980)? And to what extent does this repertoire fit with what women themselves have to say about themselves and others when they recall their stories in the city? Knowledge and readings are revealed from the narratives of these women presenting their incursions in Brasilia, whether in the domestic work or outside, in the cultural, religious, activist aspect, evidencing the different mechanisms of refusal to domestication processes imposed daily in our society